2016
DOI: 10.3109/10826084.2015.1090453
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Perpetration and Victimization as Externalizing and Internalizing Pathways: A Retrospective Study Linking Parenting Styles and Self-Esteem to Depression, Alcohol Use, and Alcohol-Related Problems

Abstract: Emerging research suggests significant positive associations between bullying and substance use behaviors. However, these studies typically focused either on the link between substance use and bullying perpetration or victimization, and few have conceptualized bullying perpetration and/or victimization as mediators. In this study, we simultaneously tested past bullying perpetration and victimization as mediational pathways from retrospective report of parenting styles and global self-esteem to current depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
2
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 84 publications
2
29
2
10
Order By: Relevance
“…According to the literature, children with lower social competence, lower self‐esteem, higher anxiety, lack of social self‐efficacy, lower self‐regard and greater withdrawal are more likely to be bullied (Guerra, Williams, & Sadek, ; Luk et al., ; Meland, Rydning, Lobben, Breidablik, & Ekeland, ; Nation, Vieno, Perkins, & Santinello, ; Navarro, Yubero, & Larrañaga, ; Perren & Alsaker, ). Despite this general profile, some differences have been found regarding the way victims react to aggression; victims are not a homogeneous group, some are passive, submissive victims, and react by crying or withdrawing, while others are aggressive victims, with a negative attitude toward violence (Brockenbrough, Cornell, & Loper, ; Olweus, ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, children with lower social competence, lower self‐esteem, higher anxiety, lack of social self‐efficacy, lower self‐regard and greater withdrawal are more likely to be bullied (Guerra, Williams, & Sadek, ; Luk et al., ; Meland, Rydning, Lobben, Breidablik, & Ekeland, ; Nation, Vieno, Perkins, & Santinello, ; Navarro, Yubero, & Larrañaga, ; Perren & Alsaker, ). Despite this general profile, some differences have been found regarding the way victims react to aggression; victims are not a homogeneous group, some are passive, submissive victims, and react by crying or withdrawing, while others are aggressive victims, with a negative attitude toward violence (Brockenbrough, Cornell, & Loper, ; Olweus, ).…”
Section: Discussionmentioning
confidence: 99%
“…O bullying "direto" caracteriza-se pela presença de agressões físicas e/ou verbais incisivas face à vítima, enquanto o bullying "indireto" consiste em as ações de isolamento ou exclusão intencional do grupo (Martins, 2005). Cabe clarificar, ainda, que o bullying na sua grande maioria das vezes é desvalorizado, na medida em que não é completamente percetível para os demais, pois certos comportamentos dos jovens são compreendidos pelos outros como condutas normativas do crescimento (Luk et al, 2016).…”
Section: Papel Dos Estilos Parentais E Da Personalidade No Desenvolviunclassified
“…De acordo com a literatura, as atitudes implementadas pelas figuras parentais no seio familiar parecem constituir aspetos importantes ao nível da regulação comportamental da população juvenil. Esta questão é corroborada pela investigação desenvolvida por Luk et al (2016) que apurou que as condutas parentais pautadas quer pela indulgência quer pela coerção física e punição estabeleciam importantes preditores dos comportamentos de bullying. Outras investigações apuraram que os jovens que desenvolvem comportamentos agressivos revelavam características ligadas ao traço de personalidade de extroversão, enquanto os jovens tidos como vítimas apresentavam maiores níveis de introversão e rejeição social (e.g., Fossati, Borroni, & Maffei, 2012).…”
Section: Papel Dos Estilos Parentais E Da Personalidade No Desenvolviunclassified
“…Studies have shown that the various parenting styles involved in parent-child relationships act as psychosocial variables capable of exerting a great influence on the adoption of diverse health-threatening behaviors among young people, including psychoactive substance use (Calafat, García, Juan, Becoña, & Fernández-Hermida, 2014;Martínez-Loredo et al, 2016). Lack of moral behavior (Nurco & Lerner, 1996), negative moral emotions, such as shame and guilt (Luk et al, 2016), physical and psychological abuse and neglect are all predictors of alcohol use by teenagers (Martínez-Loredo et al, 2016). Parental disapproval of alcohol use and a good parent-child relationship are both associated with lower levels of drinking in later adolescence (Ryan, Jorm, & Lubman, 2010).…”
mentioning
confidence: 99%
“…Various parental behaviors are associated with both the age at which a teenager begins drinking and subsequent drinking problems (Penjor, Thorsteinsson, Price, & Loi, 2019). Drug use by parents themselves, their permissive attitudes in the face of such use by their children and their incapacity to control their children are predisposing factors for initiating or continuing drug use (Berge, Sundell, Ojehagen, & Hakansson, 2016;Cablova, Csemy, Belacek, & Miovsky, 2016;Calafat et al, 2014;Luk et al, 2016;Paiva, Bastos, & Ronzani, 2012;Valente, Cogo-Moreira, & Sanchez, 2017). Lack of support and negligence on the part of parents can make adolescents more vulnerable to drug abuse, especially because this can increase the likelihood of their involvement with peers that use drugs (Martínez-Loredo et al, 2016;Valente et al, 2017).…”
mentioning
confidence: 99%